Can the complementary feeding method be a strategy to reduce the offer of ultra-processed foods? - Jordana Führ; Leandro Meirelles Nunes; Paula Ruffoni Moreira; Cátia Regina Ficagna; Renata Oliveira Neves; Juliana Rombaldi Bernardi (Elsevier, 2023)
Objective: To verify the prevalence of the offer of ultra-processed foods (UPFs), and to analyze their associated factors in the child's first year of life. Methods: Cross-sectional study with 119 mother-infant pairs. At 5.5 months of the child, the mothers received guidance on complementary feeding (CF) according to three methods: Parent-Led Weaning (PLW), Baby-Led Introduction to SolidS (BLISS), or mixed (a combination of PLW and BLISS). At nine and 12 months, the mothers answered a questionnaire about the offer of UPFs. The NOVA classification, which classifies foods according to the nature, extent, and purposes of the industrial processes to which they are subjected, was used to list the UPFs. Descriptive statistics and multivariate Poisson regression, following a multilevel hierarchical model according to the proximity to the outcome, were used to estimate the association between dependent and independent variables. Results: The prevalence of UPF consumption was 63% (n = 75) in the first year of life. Receiving guidance on healthy CF in the BLISS method showed to be a protective factor for offering UPFs (RR 0.72; CI95 0.52-0.99). Attending less than six prenatal consultations was a risk factor for the UPFs provision (RR 1.39; CI95 1.07-1.80). Conclusion: The prevalence of UPFs offered in the first year of life in this study can be considered high, and future interventions aimed at avoiding UPFs offered in this population should consider the CF method.